2020
DOI: 10.4081/ija.2020.1602
|View full text |Cite
|
Sign up to set email alerts
|

Ornamental plants for floating treatment wetlands: preliminary results

Abstract: Floating treatment wetlands (FTWs) represent a novel ecotechnology for the treatment of different types of wastewaters in natural or artificial water bodies, through the use of traditional rooted emergent macrophyte species supported by floating rafts. Although many studies have reported the treatment performances of FTWs, showing an excellent aptitude for removing nutrients, heavy metals as well as suspended solids, the investigation of vegetation has not received much attention up to now, especially for herb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Species Phragmites australis, Iris pseudacorus, Canna indica, Alissma plantago, Menianthes trifoliata and Iris sibirica showed a potential for accumulation of Cr and Ni in their below-ground parts grown in oating treatment wetlands (Čule et al 2021). The results clearly indicated that Canna indica, Pontederia cordata and Thalia dealbata are among species that were the most suitable species for CWs (Barco and Borin 2020). In a study with an arti cial pond constructed with two topsoils collected from the Portman Bay (SE Spain), species Juncus effusus L. and Iris pseudacorus L. were highly recommended for remediation purposes.…”
Section: Introductionmentioning
confidence: 98%
“…Species Phragmites australis, Iris pseudacorus, Canna indica, Alissma plantago, Menianthes trifoliata and Iris sibirica showed a potential for accumulation of Cr and Ni in their below-ground parts grown in oating treatment wetlands (Čule et al 2021). The results clearly indicated that Canna indica, Pontederia cordata and Thalia dealbata are among species that were the most suitable species for CWs (Barco and Borin 2020). In a study with an arti cial pond constructed with two topsoils collected from the Portman Bay (SE Spain), species Juncus effusus L. and Iris pseudacorus L. were highly recommended for remediation purposes.…”
Section: Introductionmentioning
confidence: 98%